Trefftz functions as basic functions of FEM in application to solution of inverse heat conduction problem - Ciałkowski, Michał J. (Computer Assisted Methods in Engineering and Science, 2023)
The work presents the application of heat polynomials for solving an inverse problem. The heat polynomials form the Trefftz Method for non-stationary heat conduction problem. They have been used as base functions in Finite Element Method. Application of heat polynomials permits to reduce the order of numerical integration as compared to the classical Finite Element Method with formulation of the matrix of system of equations.